Oral health in the indigenous Sámi population in Norway – the dental health in the North study - Brustad, Magritt; Bongo, Ann Kristine Sara; Hansen, Ketil Lenert; Trovik, Tordis A; Oscarson, Nils; Jönsson, Birgitta (Acta Odontologica Scandinavica, 2019)
Objective : This study aims at presenting the feasibility of using the public oral health clinics in indigenous Sámi communities, as arena for a comprehensive data collection for population-based epidemiological oral health research among adults (age, 18–75 years) in a multi-ethnic setting. Material and methods : The study design was cross-sectional. The data collection was incorporated into the clinical procedure at six public dental clinics situated in the Administrative Area for the Sámi Language in Finnmark County, Northern Norway, during 2013–2014. Both clinical- and questionnaire-data were collected. The quality of clinical data was thoroughly calibrated and validated. Results : Altogether, 2235 people participated in the study gave a crude response rate at 88.7%. In the final data sample ( n = 2034), 56.9% were female. We constructed three ethnic groups (Sámi, Mixed Sámi/Norwegian and Norwegian). Altogether, 67.7% reported Sámi or mixed Sámi ethnicity. The internal validity of the clinical data was found to be satisfactory when assessed by comprehensive quality procedure, calibration and reliability assessments. Conclusion : This study design and method assessments provide solid documentation that public dental clinics are suitable as arenas for data collection in epidemiological oral health studies in the Sámi population in this region.